Fropofol prevents disease progression in mice with hypertrophic cardiomyopathy. Issue 6 (19th August 2019) - Huang, Yiyuan; Lu, Haisong; Ren, Xianfeng; Li, Fazhao; Bu, Weiming; Liu, Wenjie; Dailey, William P; Saeki, Harumi; Gabrielson, Kathleen; Abraham, Roselle; Eckenhoff, Roderic; Gao, Wei Dong
Abstract: Aims : Increased myofilament contractility is recognized as a crucial factor in the pathogenesis of hypertrophic cardiomyopathy (HCM). Direct myofilament desensitization might be beneficial in preventing HCM disease progression. Here, we tested whether the small molecule fropofol prevents HCM phenotype expression and disease progression by directly depressing myofilament force development. Methods and results : Force, intracellular Ca 2+, and steady-state activation were determined in isolated trabecular muscles from wild-type (WT) and transgenic HCM mice with heterozygous human α-myosin heavy chain R403Q mutation (αMHC 403/+). αMHC 403/+ HCM mice were treated continuously with fropofol by intraperitoneal infusion for 12 weeks. Heart tissue was analysed with histology and real-time PCR of prohypertrophic and profibrotic genes. Fropofol decreased force in a concentration-dependent manner without significantly altering [Ca 2+ ]i in isolated muscles from both WT and αMHC 403/+ HCM mouse hearts. Fropofol also depressed maximal Ca 2+ -activated force and increased the [Ca 2+ ]i required for 50% activation during steady-state activation. In whole-animal studies, chronic intra-abdominal administration of fropofol prevented hypertrophy development and diastolic dysfunction. Chronic fropofol treatment also led to attenuation of prohypertrophic and profibrotic gene expression, reductions in cell size, and decreases in tissue fibrosis. Conclusions : Direct inhibition of myofilament contraction by fropofol prevents HCM disease phenotypic expression and progression, suggesting that increased myofilament contractile force is the primary trigger for hypertrophy development and HCM disease progression.